2020
DOI: 10.31838/jcr.07.03.108
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Trial Comparison of Analgesic Effect of Morphine Along With Different Doses of Ketamine and Prescription of Morphine Alone for Controlling Pain in Trauma Patients

Abstract: Introduction: Effective pain control with minimal side effects is one of the most important tasks of emergency physicians in trauma patients. In this randomized clinical trial, the effect of low doses of ketamine in trauma patients with moderate to severe pain were compared with morphine sulfate. Materials and Methods: This double-blind clinical trial study was conducted in three academic hospitals. Trauma patients (acute limb trauma) over 18 years old with moderate to severe pain (VAS≥5) were assigned into th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Two studies reported patient satisfaction on a 5-point Likert Scale rated as very low, low, fair, good or excellent. 40 41 The pooled estimate suggested a significant difference in mean patient satisfaction with pain control favouring adjuvant SDK (MD 0.56; 95% CI 0.35 to 0.76) (see online supplemental figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Two studies reported patient satisfaction on a 5-point Likert Scale rated as very low, low, fair, good or excellent. 40 41 The pooled estimate suggested a significant difference in mean patient satisfaction with pain control favouring adjuvant SDK (MD 0.56; 95% CI 0.35 to 0.76) (see online supplemental figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Five studies reported the mean age of patients ranging from 31.6 years 43 to 42.5 17 years. Three studies examined patients with an acute pain score ≥3, 45 ≥5 44 or ≥6 17 out of 10 on an 11-point Numerical Rating Scale (NRS), two studies examined patients with limb trauma, 40 43 two studies examined patients with renal colic and NRS ≥6 39 42 and one study examined patients with long bone fractures and NRS ≥7. 41 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations